Chemical composition and bioactivities of germinated Bajong brown rice / Sandra Simba Connel Bajut - Connel Bajut, Sandra Simba (2022)
Brown rice contain more nutritional components than ordinary white rice. The purpose of this study is to determine the optimized condition for rice germination, the presence of bioactive compound and antioxidant properties in Bajong brown rice. The chemical composition and bioactivities of germinated brown rice which is total phenolic compound (TPC), total flavonoid compound (TFC) and DPPH were determined by UV-Visible spectrometer while the presence of functional group of gamma-aminobutyric acid (GABA) was analyzed using fourier transform infrared (FTIR). In this study, brown rice was soaked in water for 6, 12, and 24 hours at room temperature. Brown rice was soaked to get the germinated (sprout) of the brown rice. Therefore, the fastest germination is after 24 hours of soaking due to the completely wetted of the brown rice. The total flavonoid for 6, 12 and 24 hours of germinated brown rice was 1.2839, 1.2540 and 0.9047 mg GE/g. Next, the total phenolic content in 6, 12 and 24 hours of germinated brown rice was 474.291, 472.197 and 476.197 mg GAE/g. The highest DPPH content in germinated brown rice was 3.96%. Furthermore, functional group of GABA was found in germinated brown rice where the sample was being compared to the standard of GABA.